Bullous drug eruption after second dose of mRNA-1273 (Moderna) COVID-19 vaccine: Case report - Joyce Kong; Francisco Cuevas-Castillo; Mahmoud Nassar; Chi M. Lei; Zarwa Idrees; William C. Fix; Caroline Halverstam; Adnan Mir; Amira Elbendary; Alwin Mathew (Elsevier, 2021)
Background: In December 2020, Moderna released the mRNA-1273 vaccine. The most common side effects are headache, muscle pain, redness, swelling, and tenderness at the injection site. In addition, there have been dermatological adverse events, such as hypersensitivity reactions. Although rare, various bullous eruptions have been described following vaccination. Bullous pemphigoid has been reported to occur most often after receipt of influenza and the diphtheria-tetanus-pertussis vaccine. To the best of our knowledge, there have been no reports of bullous drug eruptions resulting from mRNA vaccines. Case summary: A 66-years-old obese Guyanese male presented with a bullous rash following receipt of a commercial COVID-19 mRNA vaccine. He received the first dose uneventfully. However, within 24 h of receiving the second dose, he developed fever, myalgias, and malaise accompanied by a painful blistering rash of his torso, arms, and legs. His fever and myalgias improved after 24 h, but his painful rash did not, and five days after the initial symptoms, he presented to the hospital. There were many violaceous, poorly demarcated patches on his trunk, arms, and thighs on examination, many of which had large flaccid bullae within, and a few areas on his buttocks, posterior shoulder, and scrotum were eroded. The exam was also significant for lower extremity muscle tenderness, stiffness with preserved strength. A skin biopsy showed epidermal necrosis and sparse perivascular dermatitis concerning Stevens-Johnson syndrome or erythema multiforme. However, in the absence of mucous membrane involvement or targetoid lesions, the diagnosis of an extensive bullous fixed drug eruption was made. Conclusion: This case illustrates that the bullae eruption occurred as a result of receiving the Moderna vaccination.